Hydronephrosis in patients with cervical cancer is an indicator of poor outcome: A nationwide population-based retrospective cohort study. Issue 6 (12th February 2021) - Yang, You-Rong; Chen, Szu-Ju; Yen, Pin-Yeh; Huang, Chi-Ping; Chiu, Lu-Ting; Lin, Wu-Chou; Chen, Huey-Yi; Chen, Yung-Hsiang; Chen, Wen-Chi
Abstract : Abstract: Cervical cancer is a common malignancy in women. The presence of hydronephrosis in patients with cervical cancer can be a challenging clinical problem. The appropriate management of these patients and the prediction of their outcomes are concerns among gynecologists, urologists, medical oncologists, radiation oncologists, and nephrologists. We enrolled a total of 2225 patients with cervical cancer over a 12-year period from the nationwide database of Taiwan's National Health Insurance Bureau. Among them, 445 patients had concomitant hydronephrosis. The remaining 1780 patients without hydronephrosis were randomly enrolled as a control group for the analysis of associated factors. The results indicated that the proportions of patients with hypertension, chronic kidney disease, and diabetes were significantly higher in the hydronephrosis group. The hydronephrosis group showed a higher all-cause mortality than the non-hydronephrosis group (adjusted hazard ratio 3.05, 95% confidence interval 2.24–4.15, P  < .001). The rates of nephrectomy and stone disease were also significantly higher in the hydronephrosis group. A higher percentage of other cancers was also observed in the hydronephrosis group than in the non-hydronephrosis group (12.36% vs 8.99%, respectively). This study shows that cervical cancer with hydronephrosis may have a higher morbidity and mortality than cervical cancer without hydronephrosis. Other factors such as human papilloma virus vaccination, smoking, and cancer staging need to be further studied.